Ariane et la Clef d’Or - Brunel, Pierre (Amaltea. Revista de Mitocrítica, 2016)
Paul Dukas’ work cannot be reduced to his most famous piece, L’Apprenti sorcier. Having also published in many journals, he stands out as an author with original and individual style different from Debussy’s. In Arianne et Barbe-Bleue, maliciously considered as just a response to Pelléas et Mélisande, his biggest concern remains the transformation into music of Maeterlinck’s poem, the way of bringing the internal music out of written language.